(untitled) (Research, Society and Development, 2024)
Objective: To identify the scientific evidence available on nutritional conducts to prevent the aggravation and treat institutionalized elderly people with sarcopenia. Methods: Integrative review conducted in the databases: LILACS, PUBMED, EBSCO and SciELO, from the descriptors: Diet Therapy; Elderly; Long-Stay Institution for the Elderly; Sarcopenia. The PICO strategy was used to develop the guiding question. Articles that answered the guiding question "what is the available evidence on nutritional management for institutionalized elderly people with sarcopenia to prevent the worsening and treatment of the disease" were included. Literature review: Six articles that responded to the theme were included in the integrative review. It was found that oral supplements plus high quality protein, vitamin D, Medium Chain Triglycerides (MCTs), beta-hydroxy-beta-methylbutyric acid (HMB) and leucine were nutritional interventions used to prevent the aggravation and treat sarcopenia in institutionalized elderly people. The practice of physical exercises was considered as an alternative intervention combined with nutritional conducts in order to improve results. Conclusion: Nutritional interventions of oral supplementation of high quality protein, vitamin D, TCMs, HMB and leucine may be beneficial to prevent the onset of sarcopenia and to treat institutionalized elderly people with sarcopenia.